Studi Kelayakan Ekonomi Pengembangan Pabrik Pakan Ternak di Sulawesi Tenggara - Pagala, Muhammad Amrullah (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2010)
A descriptive feasibility study was undertaken that aimed to examine the established of Feed Mill in Southeast Sulawesi Province based on the sociocultural and socio-economic condition. The research conducted at Konawe Selatan District from April until September 2010. Research method consisted of preparation, pre-survey, survey, SWOT analysis, and Socioeconomic analysis. The result of this research showed that established of feed mill at Morome village on Konawe Selatan District was a suitable location. There were support factors as land size, forage sources, and the strategy of position was near with UPTD Peternakan, breeding activity, and area market.